Dynamics of Skill Transfer Procedures in the Electrical Industry: a comparative study in France and Japan - Lanciano, Emilie; Shuto, Wakana (Management international / International Management / Gestiòn Internacional, 2014)
French and Japanese firms have been characterised by peculiar employment systems and HR practices, and the dominance of Internal Labour Markets. The demographic context but also successive employee reductions oblige firms to adapt their HR practices and carry out changes. How do these changes of the demographic and economic context affect the process of skill transfer? This paper is a comparative analysis of the dynamics of skill transfer in the electrical manufacturing industry in France and Japan. We underline a common trend toward a formalization of skill transfer procedures and the disconnection between work activities and skill transfer.